2015
DOI: 10.1002/bdd.1988
|View full text |Cite
|
Sign up to set email alerts
|

Kidney function changes with aging in adults: comparison between cross‐sectional and longitudinal data analyses in renal function assessment

Abstract: The study evaluated whether the renal function decline rate per year with age in adults varies based on two primary statistical analyses: cross-section (CS), using one observation per subject, and longitudinal (LT), using multiple observations per subject over time. A total of 16628 records (3946 subjects; age range 30-92 years) of creatinine clearance and relevant demographic data were used. On average, four samples per subject were collected for up to 2364 days (mean: 793 days). A simple linear regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The present study identified that advanced age (≥75 years) was an independent risk factor of developing AKI after one-stop HCR, and the risk of postoperative AKI increases significantly in elderly patients (OR 5.44, P=0.014). It is well-accepted that renal function declines with age (27,29,30). Consistent with the literature, the mean eGFR in (31)(32)(33).…”
Section: Discussionsupporting
confidence: 81%
“…The present study identified that advanced age (≥75 years) was an independent risk factor of developing AKI after one-stop HCR, and the risk of postoperative AKI increases significantly in elderly patients (OR 5.44, P=0.014). It is well-accepted that renal function declines with age (27,29,30). Consistent with the literature, the mean eGFR in (31)(32)(33).…”
Section: Discussionsupporting
confidence: 81%
“…A normal adaptive renal functional response to nephrectomy involves an immediate (< 1 week) increase of approximately 40% in renal blood flow and GFR [31,32]; these changes are sustained through the early postdonation (≈ 1 year) and late postdonation (≈ 6 years) periods [33]. The age-related decline in GFR, primarily initiated after the age of 40 years, is shown to be approximately 1 mL/min/y [34][35][36]. In our study, we found a significant correlation between donor age and iohexol GFR.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, although the cross-sectional study design can propose causal links, it cannot establish credible causality. Moreover, Chung et al recommended longitudinal analysis to estimate and predict renal function decline rate with aging [38]. To overcome the abovementioned limitations, a prospective cohort study with a larger sample size including several populations is required.…”
Section: Discussionmentioning
confidence: 99%